Overview of Stunting Risk Factors in Toddlers in RT 02 and RT 04Simpang Pasir Village, Palaran District, Samarinda City. - Vanessa Vanessa; Irfansyah Baharuddin Pakki (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Stunting is a condition of chronic nutritional problems that causes failure to thrive in children and brain development is not in accordance with children at the age they should be. Stunting is a chronic malnutrition problem caused by inadequate nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. Objective : The problem of stunting which is currently a problem has an impact on various aspects, one of which is a decrease in the productivity of Human Resources (HR) in an area. Based on the results of the Indonesia Nutrition Status Survey (SSGI) in 2021 conducted by the Ministry of Health, the stunting prevalence rate in Indonesia in 2021 was 24.4%, or decreased 6.4% from 30.8% in 2018. This study aims to determine the description of factors the risk of stunting in children under five in RT 02 and RT 04 Simpang Pasir Village, Paran District, Samarinda City. Research Methods/ Implementation Methods : This type uses a cross sectional design, with a total sample of 20 samples. Data was collected using an instrumental questionnaire and then performed univariate analysis and descriptive test. Results : The results obtained are to know the risk factors regarding stunting in toddlers in the area of RT 02 and RT 04 Simpang Pasir Village, Paran District, Samarinda City. Conclusion/Lesson Learned : Based on the results of research conducted in the neighborhood units (RT) 02 and 04 of Simpang Pasir Village, Paran District, Samarinda City, it can be concluded that several risk factors contribute to stunting in toddlers. Through a cross-sectional design approach and univariate and descriptive analyses of 20 samples, it was found that stunting remains a chronic nutritional problem that impacts children's physical growth and brain development. These findings reinforce the importance of meeting nutritional needs from an early age and appropriate interventions to reduce stunting prevalence rates, especially at the smallest level, such as neighborhood associations.